Visualizing large-scale genomic sequences. - Glusman, G.
We discuss the GESTALT Workbench, which we have developed for large-scale genomic sequence data, with strong emphasis on the production of enriched graphical representation of the analysed data. It cam execute a variety of external analysis programs (e.g. gene recognition) as well as internal analyses (e.g. computational complexity).
Keywords: GESTALT Workbench; Web-based user interface; Annotation; Browser; Computational complexity; Enriched graphical representation; External analysis; Gene recognition; Interactive genome graphs; Internal analysis; Large-scale genomic sequences; Pictorial output; Sequence visualisation